Sweets, Sex, or Self-Esteem? Comparing the Value of Self-Esteem Boosts with Other Pleasant Rewards - Bushman, Brad J. (2011)
Many people ascribe great value to self-esteem, but how much value? Do people value self-esteem more than other pleasant activities, such as eating sweets and having sex? Two studies of college students (Study 1: N=130; Study 2: N=152) showed that people valued boosts to their self-esteem more than they valued eating a favorite food and engaging in a favorite sexual activity. Study 2 also showed that people valued self-esteem more than they valued drinking alcohol, receiving a paycheck, and seeing a best friend. Both studies found that people who highly valued self-esteem engaged in laboratory tasks to boost their self-esteem. Finally, personality variables interacted with these value ratings. Entitled people thought they were more deserving of all pleasant rewards, even though they did not like them all that much (both studies); and people who highly value self-esteem pursue potentially maladaptive self-image goals, presumably to elevate their self-esteem (Study 2).